PRAGMATIC FEATURES OF FAMILY EDUCATION TERMINOLOGY IN ENGLISH AND UZBEK - Sarvinoz Rashidova (European International Journal of Pedagogics, 2024)
This article explores the pragmatic features of family education-related terminology in English and Uzbek. Through an analysis of the usage of key terms in different social and cultural contexts, the study reveals how language reflects the norms, traditions, and societal structures of both cultures. The findings demonstrate that, while the core concept of family education is shared, the pragmatic applications of the terms differ significantly due to the diverse cultural frameworks.